Engineering Consulting Technology in Production Engineering Intelligent Mobile Machines - Kovalevskyy, Sergiy; Kovalevska, Olena; Dašić, Predrag; Ješić, Dušan; Kovač, Pavel (International Journal of Industrial Engineering and Management, 2017)
The article features layout tools with parallelstructure. It also developed dynamic simulation model that allows the simulation of a given law of motion of platform parallel mechanism and obtained such valued characteristics as speed, acceleration platform, changing the torque on the front crank, reactionary force kinematics of interaction mechanism of nodes. It allows you to make a decision of direct and inverse problems of dynamics by interactive visualization of spatial states of all moving parts of the implementation of precision movements programmed by many systems of coordination of movement. The article also provides the classification and analysis of prospects for the use of automated manufacturing equipment based on industrial platforms with mechanisms of parallel structure. It is established that the use of machines-robots based on these mechanisms can significantly increase the productivity and precision in machining geometrically complex engineering products. Article history: Received (02.10.2017); Revised (26.10.2017); Accepted (09.11.2017)